The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/jsfa.10454
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × environment interactions for grain iron and zinc content in rice

Abstract: BACKGROUNDNutrient deficiency in humans, especially in children and lactating women, is a major concern. Increasing the micronutrient concentration in staple crops like rice is one way to overcome this. The micronutrient content in rice, especially the iron (Fe) and zinc (Zn) content, is highly variable. The identification of rice genotypes in which there are naturally high Fe and Zn concentrations across environments is an important target towards the production of biofortified rice.RESULTSPhenotypic correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 59 publications
1
10
1
Order By: Relevance
“…In this study, the genomic heritabilities spanned a wide range from 0.14 to 0.62 (Table 2), which enabled the evaluation of the performance of MT models under contrasting levels of genomic heritability. The genomic heritability of Zn was the lowest (h 2 = 0.14, Table 2), which contradicts several previous studies that reported moderate to high heritability of Zn (Norton et al, 2010;Pinson et al, 2015;Naik et al, 2020). The poor heritability estimate of Zn in this study could be due to potential environmental effects.…”
Section: Factors Affecting the Observed Prediction Accuracies: Trait ...contrasting
confidence: 99%
“…In this study, the genomic heritabilities spanned a wide range from 0.14 to 0.62 (Table 2), which enabled the evaluation of the performance of MT models under contrasting levels of genomic heritability. The genomic heritability of Zn was the lowest (h 2 = 0.14, Table 2), which contradicts several previous studies that reported moderate to high heritability of Zn (Norton et al, 2010;Pinson et al, 2015;Naik et al, 2020). The poor heritability estimate of Zn in this study could be due to potential environmental effects.…”
Section: Factors Affecting the Observed Prediction Accuracies: Trait ...contrasting
confidence: 99%
“…In irrigated method, the GCA effect of SPY and grain Fe and Zn contents were observed in contrasting manner. Negative correlation and negative GCA effect was observed between grain yield and Fe & Zn content under irrigated and aerobic method indicates the need for Fe and Zn content improvement of parental lines in line with grain yield 19 .…”
Section: Discussionmentioning
confidence: 95%
“…Although various studies on maize and spring wheat have proven the effectiveness of the GP-based approach for kernel zinc concentration, to our knowledge no study applying GP to rice for grain zinc concentration has yet been reported. Grain zinc concentration is a complex trait greatly influenced by soil and other associated factors ( Jin et al 2013 ; Hindu et al 2018 ; Velu et al 2018 ; Naik et al 2020 ), so there are great hopes that GP will simplify the process of breeding rice for nutritional quality. On average, the PA for ZN in a single environment was low (0.26 and 0.24, for 2017 and 2018, respectively).…”
Section: Discussionmentioning
confidence: 99%